Stepping Up Skills in Urban Ghana : Snapshot of the STEP Skills Measurement Survey - Darvas, Peter (Washington, DC: World Bank, 2017)
The Skills Toward Employment and Productivity (STEP) Survey is an initiative of the World Bank in cooperation with other development partners and nongovernmental agencies and carried out in more than 14 countries globally. In Ghana, the first phase of the survey focusing on adults in urban communities was carried out in cooperation with the University of Ghana’s Institute of Statistical, Social, and Economic Research (ISSER), the Ministry of Education, the Council for Technical and Vocational Education and Training (COTVET), and the Ghana Statistical Service (GSS).